Genotyping of ESBL Producing Uropathogenic Escherichia coli in West of Iran - Parviz Mohajeri; Gita Darfarin; Abbas Farahani (International Journal of Microbiology)
Background and Objective. Urinary tract infection (UTI) is one of the most common bacterial infections in the world. Molecular fingerprinting of UTI isolates such as pulsed-Field Gel Electrophoresis using for Clonal distribution and determine of predominant type. The aim of the study was to determine genotyping of ESBL producing UPECs. Material and Methods. 200 UPEC isolates from outpatients with UTI were obtained. Antimicrobial susceptibility and interpretation were performed by disk diffusion. Virulence factors for UPECs were screened by using PCR. UPECs were analyzed by Pulsed-Field Gel Electrophoresis and images analyzed by Phoretix1DPro software. Results. A total of 200 isolates of UPECs, 24.5% (n=49) of isolates, were positive for ESBL production. Resistance ranged from 0% for amikacin and imipenem to over 93.9% for carbenicillin and ampicillin. Frequencies of haemagglutination, haemolysin, and hydrophobicity were 51%, 18.3%, and 14.28%, respectively. A total of 10 different genotypes were obtained, which include nine common clones and one single clone. Conclusion. We confirmed the prevalence of virulence phenotyping especially Haemagglutination among UPEC strains and that it can also contribute to virulence in these strains. Large diversity in genotypes was observed in the isolates that could be indicative of different sources of infection in community acquired.